Diferencias de iluminación en diferentes tipos de resinas compuestas de nanopartícula - Ferreto, Isabel; Lafuente, David; Loría Masís, Andrea; Rojas Alfaro, Alejandra (Odovtos - International Journal of Dental Sciences, 2011)
The present study evaluated changes in the Value of color (L*) in different types of nano-filled composites. Esthet-X, TPH3 (Dentsply), Filtek Z-350 (3M-ESPE) and Tetric N-Ceram (Ivoclar-Vivadent) was used in the study. 5 composites discs were made for each of the types in A2, A3 and A3.5 shades, (N=60). Sample dimensions were 3mm thick and 15 mm in diameter. Samples were measured in the Gretag Macbeth spectrophotometer under D65 light in reflectance mode, against white background. Results showed that most of the composites had a similar L* value and their differences are not statistically significant.